FREQUENCY OF HEPATORENAL SYNDROME IN CHRONIC HEPATITIS C PATIENTS ADMITTED AT CHANDKA MEDICAL COLLEGE AND HOSPITAL, LARKANA (The Research of Medical Science Review, 2025)
Objective: This study aimed to determine the frequency of hepatorenal syndrome among chronic hepatitis C patients admitted to Chandka Medical College, Larkana. Background: Hepatorenal syndrome (HRS) is a severe and potentially fatal complication that occurs in patients with advanced liver disease, including those with chronic hepatitis C. It is characterized by progressive renal dysfunction in the absence of other identifiable causes of kidney injury. The pathophysiology involves complex hemodynamic changes triggered by liver failure, leading to renal vasoconstriction and impaired kidney function. Understanding the frequency of HRS in chronic hepatitis C patients is essential for timely diagnosis and management to improve outcomes. Methodology: A cross-sectional study was conducted over six months at the Department of Medicine, SMBBMU, Larkana. Eligible patients with chronic hepatitis C provided informed consent and underwent clinical evaluation. Blood samples were collected to measure serum creatinine levels, and renal ultrasounds were performed to assess kidney morphology. Diagnosis of HRS was based on elevated creatinine and compatible ultrasound findings. Data were recorded electronically for analysis. Results: A total of 141 patients were enrolled, with a mean age of 49.5 ± 12.4 years. Females comprised 75.2% (n=106) and males 24.8% (n=35). Hepatorenal syndrome was diagnosed in 39.0% (n=55) of patients, indicating a high prevalence in this population. Conclusion: Hepatorenal syndrome is a common complication in patients with chronic hepatitis C, underscoring the need for vigilant monitoring and early intervention. Further research is warranted to explore the underlying mechanisms and develop targeted therapies to improve prognosis in this vulnerable group.